A comprehensive review of edible bird's nest. (February 2021) - Dai, Yuwei; Cao, Jie; Wang, Yuye; Chen, Yuejuan; Jiang, Lin
Graphical abstract: Highlights: Descriptions of the processing of EBN and the current situation of its industry. Descriptions of EBN's composition differences with different processing methods. Review of the latest developments of EBN's pharmacology and quality control. The challenges and future prospects of the further researches on EBN. Abstract: Edible bird's nest (EBN) is built by seven species of Aerodramus and Collocalia ( Apodidae ), using salivary gland secretion mixed with feathers or grass during the breeding. Its rich nutritional values such as anti-aging activity, immunomodulatory and antioxidant activity make consumers flock to it. Consumers' pursuit, on the one hand, aroused the arrogance of counterfeiters, which eventually leads to food safety problems. On the other hand, it promotes the in-depth studies of EBN in all aspects, such as compositions, biological activities, authenticity identification, quality control, and so on. This paper presented the origins and classifications of EBN and the current situation of EBN industry in detail; reviewed the nutritional compositions, pharmacological actions, identification, inspection and content determination of EBN comprehensively; and prospected the future research directions to provide suggestions for the further study.